2017
DOI: 10.1111/1365-2745.12731
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric N:P flexibility and mycorrhizal symbiosis favour plant resistance against drought

Abstract: Summary Drought induces changes in the nitrogen (N) and phosphorus (P) cycle but most plant species have limited flexibility to take up nutrients under such variable or unbalanced N and P availability. Both the degree of flexibility in plant N:P ratio and of root symbiosis with arbuscular mycorrhizal fungi might control plant resistance to drought‐induced changes in nutrient availability, but this has not been directly tested. Here, we examined the role of plant N:P stoichiometric status and mycorrhizal symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 66 publications
5
73
1
1
Order By: Relevance
“…, Mariotte et al. ). For instance, there are a growing number of studies that have shown that drought reduces the mobility of soil nutrients, litter decomposition, and the activity of soil microbes (Durand et al.…”
Section: Discussionmentioning
confidence: 98%
“…, Mariotte et al. ). For instance, there are a growing number of studies that have shown that drought reduces the mobility of soil nutrients, litter decomposition, and the activity of soil microbes (Durand et al.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the length of the growing season, and thus leaf longevity tend to decrease from the tropics to boreal regions, resulting in higher leaf growth rates and higher P demands, particularly in the growing season, with increasing latitude [41,46]. Furthermore, soil P availability relative to N availability tends to increase with increasing latitude or from the humid to arid regions, resulting in decreasing leaf N:P ratios [10,31,32,47]. These trends help to explain why the numerical values of the N vs. P scaling exponent decline from the tropics to higher latitudes for each of the major plant functional groups.…”
Section: Possible Mechanisms Of the Different N-p Scaling Exponentsmentioning
confidence: 99%
“…Both nutrients are recycled via the decomposition of soil organic matter 17 . Although soil nutrients and microbiota are the main drivers of leaf nutrient concentrations 21, 22 , other soil properties and processes (for example, soil moisture and soil salt content) also determine the availability of nutrients to plants 2325 . A recent study showed that variation in soil characteristics had more profound immediate effects on plant stoichiometry than did climate at the regional scale 26 .…”
Section: Introductionmentioning
confidence: 99%